STRAWBERRY MARKETING MIX IN DOLAT RAYAT VILLAGE, KARO REGENCY - Nur hayati; Mawardati; Muhammad Authar; Cut Rozana Sari; Barmawi (LPPM Universitas Malikussaleh - Indonesia, 2026)
Strawberries (Fragaria sp.) are a high-value horticultural commodity, yet marketing performance in Dolat Rayat Village, Karo Regency remains far from optimal. This study aims to analyze the implementation of the 7P marketing mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) applied by strawberry farmers in Dolat Rayat Village, Karo Regency. The research was conducted from October to November 2025. Data were collected through in-depth interviews and field observations of 13 farmers selected through purposive non-probability sampling based on the largest land area criteria (0.5 ha and 0.7 ha) from a total population of 92 farmers. Data analysis used the qualitative descriptive method with Miles and Huberman's (1994) interactive model, consisting of data reduction, data presentation, and conclusion drawing, verified through triangulation. Results show that the product element demonstrates relative strength: farmers use the mencir variety producing large fruit (diameter 3-4 cm, weight 15-25 grams), consistent sweet taste, and shelf life of 2-3 days at room temperature and 5-7 days refrigerated, with optimal adaptation to local climate conditions. The place element is also favorable, with gardens located strategically along the main village road with good vehicle accessibility. However, the remaining five elements remain underdeveloped.